Trading Saham Based on Fatwa DSN-MUI No.135/DSN-MUI/V/2020 for Trader: Trading Saham Berdasarkan Fatwa DSN-MUI No.135/DSN-MUI/V/2020 - Ummi Kalsum, Ummi; Anggriani, Freti (Tawazuna, 2022)
This article aims to provide a deeper knowledge of the laws of stock trading that are found not only in traditional activities but also in Shariah activities. The method used for the discussion is a Library Research method that collects data from multiple written sources, such as books and other articles related to discussions related to stock trading. In Indonesia itself this is a new phenomenon on the rise and many people are seeing this trend so they can benefit from it in the short term. It is a transaction that buys and sells securities, and is different from stock investment that a long-term transaction (savings). Equity trading activities in accordance with DSN-MUI Fatwa No. 135/DSN-MUI/V/2020 on equities, It explains to traders the importance of stocks, laws, issuances and where stocks are traded.